Differences in stress levels between wild-caught and captive born Asian elephants - Nieminen, Aleksi (My University, 2023)
Wild capture of animals remains, among other uses, important for maintaining genetically healthy and viable captive populations. The capture process is often very stressful and potentially risky, with potentially far-reaching and long-term effects on the health and welfare of the captured animals such as increased mortality and lowered fertility. This thesis aims to shed light into the underlying physiological factors behind such issues, as shown in previous studies on wild-caught Asian elephants (Elephas maximus) that are used as labour in Myanmar timber camps. This was done by analysing data collected from elephant faecal samples and measuring the concentrations of faecal glucocorticoid metabolites (FGM) in them. Results showed seasonal variation of FGM concentrations, with FGM concentrations being higher in the hot season compared to the cold season. Furthermore, the age of the elephants from the studied population had significant effects on their FGM concentrations with retired elephants having lower FGM concentrations than working elephants or elephants in training and elephants in training showing the highest FGM concentrations. However, whether the elephants were wild-caught, or captive born did not show significant effects in the analysed data. Harmful stress-related long-term effects were not found by this study, although the limited scope of the study combined with comparisons to previous studies means their existence cannot be ruled out completely. Further research into elephant stressors and stress hormone levels using a broader group of potentially significant factors is therefore advised.
Keywords: Key words: Elephas maximus; elephant age; faecal glucocorticoid metabolites; seasonal variation; stress; wild capture